Consideration of insulation coordination in power converters: basic terminology and review of standards in the field - Despotović, Željko V (Proceedings, Electrical engineering institute "Nikola Tesla", 2021)
Insulation coordination in the field of power electronics has become a very important element for the design and implementation of various topologies of power converter modules and devices, and therefore certainly deserves the attention of both designers and users of these devices. Over decades of experience in this area, a lot of experiential and practical data has been collected regarding insulation coordination, which is documented in several key standards. The paper presents the basic terminology and basic types of insulation used in power converters, as well as an overview of relevant standards in the field of insulation coordination from the aspect of design and use of power converters. In addition to the interest for designers, the insulation coordination of the power converters has become a very important element for users, but also for the realization and implementation of different converter topologies.
Keywords: insulation coordination, power converters, clearance, overvoltage, creepage